Social-Cultural, Traditional Beliefs, and Health System Barriers of Hepatitis B Screening among Hmong Americans: A Case Study - Fang, Dao Moua (Cancer, 2018)
BACKGROUND: The Hmong experience a five-times higher incidence rate of liver cancer than non-Hispanic Whites and there is a low hepatitis B screening rate (24%) among Hmong adults compared to other Asian Americans. The purpose of this study was to examine the Hmong’s perceptions on social-cultural determinants, traditional health beliefs, and health care system barriers that influenced community-based hepatitis B screening interventions. METHODS: A qualitative method was used, integrating a collective case study research design. In-depth interviews were used to collect data from 20 Hmong adults from the Greater Sacramento areas who participated in the Chen et al. (2013) study. A pattern matching analytic technique was used to analyze the data. The main core elements of Culture Care Theory were used to capture the key themes presented by the participants. RESULTS: Protecting a family’s reputation; fear of doctors, medical procedures, and test results; lack of trust in medical doctors and medical care services; and using Hmong herbal medicines and practicing spiritual healing were identified as social-cultural and traditional health beliefs barriers to obtaining HBV screening. Health care costs, perceived discrimination, lack of transportation, linguistic discordance, and poor quality of care were identified as barriers to accessing high quality health care services and obtaining hepatitis B screening. CONCLUSION: Providers, health policy makers, researchers, and community-based organizations will need to work together to develop intervention strategies to address the social-cultural, traditional health beliefs, and health care factors that influence obtaining hepatitis B screening in the Hmong community.